Penerapan Arsitektur Hijau Pada Rancangan Pusat Penelitian Dan Pengembangan kelapa Sawit Di Rokan Hulu - Latifah Sahroini; Yohannes Firzal; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Green Architecture is a design approach in building designing. Green Architecture treats landscape, building, and interiors as one, and is also applied as a sustainable approach on development cycle. Green Architecture on the design of Palm Oil Research and Development Center is used as a method to transform concept, principle, and design strategy that exploit surrounding area weakness into an advantage to increase the building’s function. The concept of Power of Nature is applied to the design by metaphorical approach that is a combination of four natural elements in its interrelation to create balance. It is applied to the shape of building mass in terms of orientation, openings, roof shape, choice of color, and landscape pattern design.Keywords: Green Architecture, Palm Oil, Power of Nature